Factors affecting the depth of burns occurring in medical institutions. Issue 3 (May 2015) - Cho, Young Soon; Choi, Young Hwan; Yoon, Cheonjae; You, Je Sung
Highlights We analyzed the medical records of 115 patients with burns occurred that occur in medical institutions. The burn site and contact burns were both factors affecting the depth of the burn. The rate of deep burns was higher in patients with contact burns and with lower body burns.